Teaching Aboriginal languages : case studies - New South Wales. Board of Studies (Sydney : Board of Studies NSW, 2000)
Contains six case studies of Aboriginal language programs operating in New South Wales and the Northern Territory; provides a background to languages, who was involved in developing the programs, what the objectives and major issues were, highlights, and what was achieved.
Cover illustration: Connie Ah-See.
"99073"--verso t.p.
Includes bibliographical references ( p. 56)
Keywords: Australian languages -- Study and teaching -- New South Wales -- Case studies; Aboriginal Australians -- Languages -- Study and teaching -- New South Wales -- Case studies; Aboriginal Australians -- New South Wales -- Education -- Languages -- Case studies; Education - Language; Arrernte / Aranda language (C8) (NT SG53-02); Luritja / Loritja language (C7.1) (NT SG52-04); Ngiyambaa / Ngemba language (D22) (NSW SH55-10); Muruwari / Murrawarri language (D32) (NSW SH55-06); Wiradjuri language (D10) (NSW SI55-07); Gumbaynggir / Gumbainggirr language (E7) (NSW SH56-11); Gamilaraay / Gamilaroi / Kamilaroi language (D23) (NSW SH55-12); Warlpiri language (C15) (NT SF52-04); Yuwaalaraay / Euahlayi / Yuwaaliyaay language (D27) (NSW SH55-07); Bowraville (NSW N Coast SH56-10); Mparntwe / Alice Springs (South Central NT SF53-14); Brewarrina (N NSW SH55-06); New South Wales (NSW); Walgett (N NSW SH55-11); Wagga Wagga (SW NSW SI55-15)